An investigation of drugs abuse in sport performance - Mazzeo, F.; Raiola, G. (Journal of Human Sport & Exercise, 2018)
Doping in performance sport is a complex and controversial issues. The secrecy that characterizes it hinders the implementation of epidemiological investigations. It involves the entire society. Moreover, the forces that conspire behind doping have always been able not only to identify new substances and new methods but also to steal the new scientific discoveries aimed at the treatment of diseases, for their illegal purposes. The fight against doping has had a strong push, in 2004, with the birth of the first World Anti-doping Code drafted by WADA. The laboratories, the Code, the Biological Passport and the ADAMS are important tools for the fight against doping. The aim study is to show the data relating to the consumption of drugs from 2003 to 2017. A number of the commonly used substances have been discussed and their risks and side effects reviewed.